1983
DOI: 10.1111/j.1432-1033.1983.tb07785.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of glucagon on flux rates in perfused rat liver

Abstract: The relationship between inhibition of glycolysis and stimulation of oxygen consumption by glucagon was studied in perfused rat livers. The two effects exhibit similar kinetics and dose-response curves; they are slower and less sensitive to the glucagon concentration than the stimulatory effect on glycogenolysis. A stoichiometry of 1 mol extra oxygen consumed/l.8 mol of diminished lactate plus pyruvate production was found. Under conditions where glucagon did not cause a marked inhibition of glycolysis (i.e. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The consumption rate for the small intestine compared well with results obtained in intestinal perfusions with red blood cells [6,[10][11][12]. In isolated liver perfusions with erythrocyte-free media the oxygen uptake was between 2 and 2.5 ,mol/min per g [13][14][15][16][17][18].…”
Section: Functional and Morphological Integrity Of The Intestine-livementioning
confidence: 54%
“…The consumption rate for the small intestine compared well with results obtained in intestinal perfusions with red blood cells [6,[10][11][12]. In isolated liver perfusions with erythrocyte-free media the oxygen uptake was between 2 and 2.5 ,mol/min per g [13][14][15][16][17][18].…”
Section: Functional and Morphological Integrity Of The Intestine-livementioning
confidence: 54%
“…Exercise, for example, is associated with a large increase in portal venous glucagon. Glucagon increases hepatic glucose production (Hirsch et al, 1991; Lavoie et al, 1997; Wasserman et al, 1989, 1985, 1984), fat oxidation (Wasserman et al, 1995), amino acid metabolism (Halseth et al, 1998; Wasserman et al, 1988), and ureagenesis (Exton and Park, 1966; Heimberg et al, 1969; Kimmig et al, 1983; Krishna et al, 2000). More recently we showed that elevated glucagon increases the AMP/ATP ratio and activates AMPK in vivo (Berglund et al, 2011, 2009).…”
Section: Endocrine Actionmentioning
confidence: 99%
“…Glucagon is elevated and AMPK is activated under conditions uptake (Kimmig et al, 1983) and fat oxidation (Heimberg et al, 1969) are elevated. The coupled relationship in which O 2 between TCA cycling and gluconeogenesis is paralleled by a coupling of ATP formation and breakdown.…”
Section: Endocrine Actionmentioning
confidence: 99%
“…As shown in the following paper (Fig. 2 of [14]), the concentration for half-maximal effect was about three-times lower than that required for half-maximal inhibition of lactate plus pyruvate production. The data suggest that glycogen breakdown is more sensitive to stimulation than glycolysis to inhibition by glucagon.…”
Section: Experimental Protocolmentioning
confidence: 99%